Desain Teknologi Dual-Axis Solar Tracker Untuk Mengukur Sudut, Torsi dan Daya Motor Worm Gear Pada Panel Surya - Adi Mulyadi; Muhammad Zainal Roisul Amin (CV. Sekawan Siji, 2024)
This paper discusses the design of dual-axis solar tracker technology to measure the angle, torque and motor power of solar panels in dragon fruit fields in Banyuwangi Regency. The installation of solar panels that have been carried out in static conditions with the charging of solar panel energy produced is not optimal. Therefore, solar tracker technology is proposed to measure the angular velocity, motor torque, and motor power by following the direction of the sun. The dual-axis solar tracker uses a worm gear consisting of a spiral threaded shaft to drive a toothed wheel with a rotation angle of 180o. The results of the application of the solar tracker show that the angular velocity, torque and power increase significantly. Measurement of the dual-axis solar tracker with a time of 2-30 seconds obtained the angle, torque and power of the worm gear motor at a time of 0 seconds, namely -664.151 deg / s to a time of 30 seconds 621.534 deg / s. While the results of measurements with a time of 30-60 seconds produced an angular velocity of 621.534-2169.744 deg / s. Furthermore, the measurement of the worm gear motor torque at 0-30 seconds obtained 353,712-2286,268 Nm, and the measurement of the motor torque at 30-60 seconds produced a value of 2286,268-7356,913 Nm. The measurement of the worm gear motor power with a time of 2-30 seconds produced an average power of 7,785-46,984 kW, and the measurement of the motor power at 30-60 seconds produced a power of 46,984-101,479 kW.